Rapid in vitro prototyping of O-methyltransferases for pathway applications in Escherichia coli. Issue 6 (17th June 2021) - Haslinger, Kristina; Hackl, Thomas; Prather, Kristala L.J.
Summary: O -Methyltransferases are ubiquitous enzymes involved in biosynthetic pathways for secondary metabolites such as bacterial antibiotics, human catecholamine neurotransmitters, and plant phenylpropanoids. While thousands of putative O -methyltransferases are found in sequence databases, few examples are functionally characterized. From a pathway engineering perspective, however, it is crucial to know the substrate and product ranges of the respective enzymes to fully exploit their catalytic power. In this study, we developed an in vitro prototyping workflow that allowed us to screen ∼30 enzymes against five substrates in 3 days with high reproducibility. We combined in vitro transcription/translation of the genes of interest with a microliter-scale enzymatic assay in 96-well plates. The substrate conversion was indirectly measured by quantifying the consumption of the S -adenosyl-L-methionine co-factor by time-resolved fluorescence resonance energy transfer rather than time-consuming product analysis by chromatography. This workflow allowed us to rapidly prototype thus far uncharacterized O -methyltransferases for future use as biocatalysts. Graphical abstract: Highlights: We developed a time- and resource-saving qualitative screen for OMTs TXTL from linear templates eliminated time-consuming cloning Small-scale enzymatic assays were compatible with the crude TXTL reactions FRET-based readout allowed parallelized analysis of 180 assay reactions in 3 h Abstract : Methylation is an important reaction in medicinal chemistry that can be carried out by enzymes under mild conditions. Identifying the appropriate methyltransferase, however, is a resource-consuming process. Haslinger et al. developed a rapid prototyping workflow for O -methyltransferases that should be applicable to all S -adenosylmethionine-dependent methyltransferases.